요추부 추궁간 경막외 신경 차단술 후 발생한 기뇌증 - 정영우(Young-Woo Chung); 서형연(Hyoung-Yeon Seo); 이동현(Dong-Hyun Lee); 김성규(Sung-Kyu Kim) (The journal of the Korean Orthopaedic Association, 2017)
공기 저항법을 이용한 요추부 경막외 신경 차단술 시 흔하지 않지만 기뇌증을 유발할 가능성이 있다. 본 증례보고에서는 요추부 추궁간 경막외 신경 차단술 후 발생한 기뇌증에 대해 보고하고자 한다. 58세 남자 환자로 제 4-5 요추부 추간판 탈출증에 대하여 공기 저항을 이용한 요추부 추궁간 경막외 신경 차단술을 시행받았다. 환자는 경막외 신경 차단술 직후 두통, 구토 증상 및 체간의 근육간대경련을 보였다. 입원 후 두개부 컴퓨터 단층촬영을 시행하였으며 기뇌증으로 진단되었다. 보존적 치료 후 증상은 모두 회복되었으며 다른 합병증 없이 신경 차단술 후 11일째 퇴원하였다 Lumbar epidural block using a “loss of resistance” technique (LORT) with air can potentially cause pneumocephalus. Herein, we present a pneumocephalus that occurred after an epidural block. A 58-year-old male patient underwent an interlaminar lumbar epidural block using a LORT with air for L4-5 disc herniation. After the block, the patient complained of headache, vomiting, and truncal myoclonus. For further evaluation, a brain computed tomography was performed, and pneumocephalus was finally diagnosed. The patient underwent conservative treatment and recovered without any complications. He was discharged on the 11th day after the block. KCI Citation Count: 1